Dinamika Pelayanan Publik Di Bkpsdm Kota Gunungsitoli: Analisis Terhadap Prosedur Kendala Dan Rapat Evaluatif - Ndraha, Ayler Beniah; Waruwu, Eliyunus; Zega, Asokhiwa (CV. SINAR HOWUHOWU, 2024)
This research aims to analyze the dynamics of public services at the Personnel and Human Resources Development Agency (BKPSDM) of Gunungsitoli City, focusing on service procedures, obstacles faced, and the effectiveness of evaluative meetings. The research method used is a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews, and document analysis. The results showed that although BKPSDM has implemented clear public service procedures, constraints such as limited competent human resources and inadequate technological infrastructure hinder the effectiveness of services. The process of digitizing documents and the use of information technology is still limited, which causes the length of time to complete administrative services. Periodic evaluative meetings have been successful in identifying internal problems and offering improvement solutions, although the implementation of meeting results is often constrained by budget limitations. In general, the public is satisfied with the services provided, although there are criticisms related to the length of the service process. To improve service quality, this study recommends improving technological infrastructure, developing employee competencies, simplifying bureaucracy, and increasing budget allocations. By implementing these recommendations, BKPSDM is expected to improve the efficiency and responsiveness of public services.